Design and synthesis of pyrazole/isoxazole linked arylcinnamides as tubulin polymerization inhibitors and potential antiproliferative agents. Issue 40 (25th August 2015) - Kamal, Ahmed; Shaik, Anver Basha; Rao, Bala Bhaskara; Khan, Irfan; Bharath Kumar, G.; Jain, Nishant
Abstract : A series of pyrazole/isoxazole linked arylcinnamide conjugates were synthesized and investigated for their cytotoxic activity against a panel of four human cancer cell lines. Most of them have shown significant cytotoxicity apart from potential tubulin depolymerization activity. Abstract : As pyrazole and isoxazole based derivatives are well-known for displaying a considerable biological profile, an attempt has been made to unravel their cytotoxic potential. In this context, a number of pyrazole/isoxazole linked arylcinnamide conjugates (15a–o and21a–n ) have been synthesized by employing a straight forward route. The basic structure comprised three ring scaffolds (A, B and C): methoxyphenyl rings as A and C rings and a five membered heterocyclic ring (pyrazole or isoxazole) as the B-ring. To achieve clear understanding, these derivatives are categorized as pyrazole-phenylcinnamides (PP ) and isoxazole-phenylcinnamides (IP ). These compounds have been evaluated for their ability to inhibit the growth of various human cancer cell lines such as HeLa, DU-145, A549 and MDA-MB231 and most of them exhibit considerable cytotoxic effects. Some of them like15a, 15b, 15e, 15i and15l exhibit promising cytotoxicity in HeLa cells (IC50 = 0.4, 1.8, 1.2, 2.7 and 1.7 μM). Amongst them15a, 15b and15e were taken up for detailed biological studies, they were found to arrest the cells in the G2/M phase of the cell cycle. Moreover, they were investigated for their effect on the microtubular cytoskeletal system by using a tubulin polymerization assay, immunofluroscence and molecular docking studies; interestingly they demonstrate a significant inhibition of tubulin polymerization.